ÌµÍý¿ô¡Ý¼°¤ÎÃÍ£²
ÌµÍý¿ô¤Î·×»» >
¡¡Ê£¿ô¤ÎÊ¸»ú¤ò´Þ¤àÂ¿¹à¼°¤ÎÃÍ¤òµá¤á¤Æ¤ß¤Þ¤·¤ç¤¦¡£
ÎãÂê
¡¡x=(¢å31)/¢å2¡¢y=(¢å3+1)/¢å2¡¡¤Î¤È¤¡¢
¡¡x^{4}y^{3}+x^{3}y^{4} ¤ÎÃÍ¤òµá¤á¤Æ¤¯¤À¤µ¤¤¡£
¡¡x^{4}y^{3}+x^{3}y^{4}¡¡¡¡¶¦ÄÌ°ø¿ô¤Ç¤¯¤¯¤ë¡£
=(xy)^{3}(x+y)¡¡¡¦¡¦¡¦¡
¤³¤³¤Ç¡¢
¡¡xy=(¢å3^{2}1^{2})/¢å2^{2}=1
¡¡x+y=2¢å3/¢å2=¢å6
¡=1^{3}¡ß¢å6=¢å6¡¡¡¦¡¦¡¦(Åú)
Îý½¬
¡¡¼¡¤Î¼°¤ÎÃÍ¤òµá¤á¤Æ¤¯¤À¤µ¤¤¡£
Åú ¤¨
Åú ¤¨
¡¡Ê£¿ô¤ÎÊ¸»ú¤ò´Þ¤àÂ¿¹à¼°¤ÎÃÍ¤òµá¤á¤Æ¤ß¤Þ¤·¤ç¤¦¡£
ÎãÂê
¡¡x=(¢å31)/¢å2¡¢y=(¢å3+1)/¢å2¡¡¤Î¤È¤¡¢
¡¡x^{4}y^{3}+x^{3}y^{4} ¤ÎÃÍ¤òµá¤á¤Æ¤¯¤À¤µ¤¤¡£
¡ÊÌÀÂçÉíÂ°ÃæÌî¹â¡Ë 
¡¡x^{4}y^{3}+x^{3}y^{4}¡¡¡¡¶¦ÄÌ°ø¿ô¤Ç¤¯¤¯¤ë¡£
=(xy)^{3}(x+y)¡¡¡¦¡¦¡¦¡
¤³¤³¤Ç¡¢
¡¡xy=(¢å3^{2}1^{2})/¢å2^{2}=1
¡¡x+y=2¢å3/¢å2=¢å6
¡=1^{3}¡ß¢å6=¢å6¡¡¡¦¡¦¡¦(Åú)
Îý½¬
¡¡¼¡¤Î¼°¤ÎÃÍ¤òµá¤á¤Æ¤¯¤À¤µ¤¤¡£
1.  ¡¡¢å3x+¢å2y=1¡¢¢å2x+¢å3y=¢å6 ¤Î¤È¤¡¢x^{2}y^{2}  
(ÅìÂç»û³Ø±à¹â)  
2.  ¡¡(x+y)^{2}(51+10¢å2)/5¡¢xy=(15¢å2)/¢å5 ¤Î¤È¤¡¢4xy 

(ÆüÂçÂè»°¹â)  
3.  ¡¡a=(3+¢å3)/¢å2¡¢b=(2¢å2)/¢å3¡¢c=2¢å2 ¤Î¤È¤¡¢a^{2}+b^{2}c^{2} 

(Áã³û¹â)  
4.  ¡¡x=¢å61¡¢y=¢å2¢å3 ¤Î¤È¤¡¢ x^{2}+2¢å2xy+3y^{2}+3x+2¢å3y+3 

(·ÄØæµÁ½Î»ÖÌÚ¹â)  
5.  ¡¡x=¢å5+¢å3+¢å2¡¢y=¢å5¢å3+¢å2¡¢z=¢å3¢å2 ¤Î¤È¤¡¢ x^{2}2xyzx+y^{2}+yz 

(ÂçºåÀ±¸÷³Ø±¡¹â) 
Åú ¤¨
1.  ¡¡¢å3x+¢å2y=1¡¢¢å2x+¢å3y=¢å6 ¤Î¤È¤¡¢ ¡¡x^{2}y^{2} ¤ÎÃÍ 2¤Ä¤Î¾ò·ï¼°¤ò2¾è¤¹¤ë¡£ ¡¡3x^{2}+2¢å6xy+2y^{2}=1 ¡¡2x^{2}+2¢å6xy+3y^{2}=6 2¼°¤Îº¹¤«¤é¡¢ ¡¡x^{2}y^{2}=5¡¡¡¦¡¦¡¦(Åú) 

2.  ¡¡(x+y)^{2}=(51+10¢å2)/5¡¢xy=(15¢å2)/¢å5 ¤Î¤È¤¡¢4xy ¤ÎÃÍ ¡¡(x+y)^{2}=(xy)^{2}+4xy ¤«¤é¡¢ ¡¡4xy=(x+y)^{2}(xy)^{2} ¡¡¡¡ =(51+10¢å2)/5(15¢å2)^{2}/5 ¡¡¡¡ =(51+10¢å2)/5(5110¢å2)/5 ¡¡¡¡ =4¢å2¡¡¡¦¡¦¡¦(Åú) 

3.  ¡¡a=(3+¢å3)/¢å2¡¢b=(2¢å2)/¢å3¡¢c=2¢å2 ¤Î¤È¤¡¢ ¡¡a^{2}+b^{2}c^{2}¡¡¡¡ =(12+6¢å3)/2+(64¢å2)/38 =6+3¢å3+24¢å2/38 =3¢å34¢å2/3¡¡¡¦¡¦¡¦(Åú) 

4.  ¡¡x=¢å61¡¢y=¢å2¢å3 ¤Î¤È¤¡¢ ¡¡x^{2}+2¢å2xy+3y^{2}+3x+2¢å3y+3¡¡ ÏÂ¤Î2¾è¤Ë¤¹¤ë¡£ =(x^{2}+2¢å2xy+2y^{2})+y^{2}+3x+2¢å3y+3 =(x+¢å2y)^{2}+(y^{2}+2¢å3y+3)+3x =(x+¢å2y)^{2}+(y+¢å3)^{2}+3x =(¢å61+2¢å6)^{2}+(¢å2)^{2}+3¢å63 =1+2+3¢å63 =3¢å6¡¡¡¦¡¦¡¦(Åú) 

5.  ¡¡x=¢å5+¢å3+¢å2¡¢y=¢å5¢å3+¢å2¡¢z=¢å3¢å2 ¤Î¤È¤¡¢ ¡¡x^{2}2xyzx+y^{2}+yz¡¡ ÏÂ¤Î2¾è¤Ë¤¹¤ë¡£ =(x^{2}2xy+y^{2})zx+yz =(xy)^{2}z(xy)¡¡¡¡¶¦ÄÌ°ø¿ô¤Ç¤¯¤¯¤ë¡£ =(xy)(xyz) =2¢å3(¢å3+¢å2) =6+2¢å6¡¡¡¦¡¦¡¦(Åú) 
JUGEM¥Æ¡¼¥Þ¡§³ØÌä¡¦³Ø¹»
¤³¤Îµ»ö¤ËÂÐ¤¹¤ë¥³¥á¥ó¥È